Can ventricular tachycardia non-inducibility after ablation predict reduced ventricular tachycardia recurrence and mortality in patients with non-ischemic cardiomyopathy? A meta-analysis of twenty-four observational studies. (1st November 2016) - Hu, Jinzhu; Zeng, Shan; Zhou, Qiongqiong; Zhu, Wengen; Xu, Zhenyan; Yu, Jianhua; Hong, Kui
Abstract: Background: At present, the role of ventricular tachycardia (VT) non-inducibility after ablation in patients with non-ischemic cardiomyopathy (NICM) remains controversial. We conducted a meta-analysis of the published literature to assess whether VT non-inducibility after ablation could predict reduced VT recurrence and mortality in patients with NICM. Methods: PubMed, ScienceDirect, and the Cochrane library were searched for studies evaluating the effects of VT non-inducibility after catheter ablation on the long-term outcome in NICM patients with sustained VT. Results were analyzed using a fixed-effect model, and the data were pooled using RevMan 5.3 software. Results: Twenty-four observational studies were identified (736 participants, mean follow-up time: 22 months). NICM patients with VT inducibility after ablation had a higher risk of VT recurrence (odds ratio [OR] = 5.83, 95% confidence interval [CI] 4.07–8.37; P < 0.00001) and all-cause mortality (OR = 3.55, 95% CI 1.62–7.78; P = 0.002) compared with VT non-inducibility. Similarly in the subgroup analysis, patients with VT inducibility showed a higher risk of VT recurrence from non-ischemic dilated cardiomyopathy (OR = 3.92, 95% CI 2.36–6.50; P < 0.00001) and arrhythmogenic right ventricular dysplasia/cardiomyopathy (OR = 5.37, 95% CI 2.20–13.10; P = 0.0002). Additionally, meta-analysis also showed that combined endo–epicardial ablation significantly reduced the risk of VT recurrence compared with endocardial-only ablation (OR = 2.02, 95% CI 1.19–3.44; P = 0.009; mean follow-up time: 22 months). Conclusion: Recent evidence has shown that VT non-inducibility after ablation is a predictor for reduced VT recurrence and mortality compared with VT inducibility in NICM patients with sustained VT. In addition, endocardial plus adjuvant epicardial ablation provides better long-term arrhythmia-free survival than endocardial ablation alone.